Principle of non-discrimination and non-stigmatization: considerations for improving the quality of life of people with burn sequelae - Mariane Ferreira Barbosa Emerick; Katia Torres Batista (Revista Brasileira de Cirurgia Plástica)
Introduction: The increase in the survival of burn victims brought to reality the problems related to sequelae, which can generate stigmatization and discrimination and influence all aspects of the individual’s life. The objective is to analyze the principle of non-stigmatization and non-discrimination of the Universal Declaration of Bioethics and Human Rights in improving the quality of life of people with burn sequelae. Methods: Integrative review using the PICO strategy, P=patient victim of burn sequelae; I=principle of non-stigmatization; C=healthy psychosocial; Result=improvement of quality of life, for the question: How can the application of the principle of nonstigmatization and non-stigmatization help to improve the quality of life of people with burn sequelae? Results: In the last five years, 77 articles were found with the stigma and burn descriptors, and twelve were selected for analysis. The instruments for assessing stigma, stress, and self-esteem have been described. People who were victims of burn sequelae had a great psychosocial burden, stigmatization, and discrimination that persisted over time. Conclusion: In this integrative review, instruments were found to assess stigma, stress, self-esteem and assess social support. Intrinsic and extrinsic factors related to stigmatization and discrimination were identified, and considerations and reflections were presented to apply the Principle of non-stigmatization of Universal Declaration of Bioethics and Human Rights as proposed by the authors, who highlighted actions that can improve people’s social support and quality of life with burns sequelae.